El Derecho español sobre comedores de empresa: actualidad y paradojas - Sempere Navarro, Antonio V. (Revista de Derecho, 2019)
Two rulings dated 1938 established the obligation of companies to make dinnersavailable to their workers, whether this would be in the form of a place arranged forsuch purpose, or by even serving food. Since then no other state norm has taken careof the matter, discussing whether the old norms are still current.On the other hand, when workers really benefit from the company’s dinner, of lowpricefood or of restaurant tickets; all sorts of doubts rise regarding their juridicalnature.The present study revises this old institution, examining the most recent sentencesand reporting the state of the matter.
Keywords: dinners; wages in values; extra-wage benefits; restaurant tickets